Impact of E-Learning on the Academic Performance of Schools in Uganda - Kevin, Sanyu (International Journal of Online and Distance Learning, 2023)
Purpose: The objective of this study is to explore the impact of E-learning on the academic performance of schools in Uganda. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the impact of E-learning on the academic performance of schools in Uganda. From the literature reviewed, it is evident that e-learning has a significant impact on the academic performance of students in Uganda. The studies showed that e-learning can improve academic performance, motivation, and engagement among students. Furthermore, e-learning can enhance language proficiency, critical thinking skills, and proble Purpose: The objective of this study is to explore the impact of E-learning on the academic performance of schools in Uganda. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the impact of E-learning on the academic performance of schools in Uganda. From the literature reviewed, it is evident that e-learning has a significant impact on the academic performance of students in Uganda. The studies showed that e-learning can improve academic performance, motivation, and engagement among students. Furthermore, e-learning can enhance language proficiency, critical thinking skills, and problem-solving skills. Unique Contribution to Theory, Practice and Policy: The Social Cognitive Theory, Constructivism Theory and Cognitive Load Theory may be used to anchor future studies on the impact of E-learning on the academic performance of schools in Uganda. The government should provide adequate infrastructure to support e-learning, including access to electricity, computers, and the internet. E-learning should be integrated into the curriculum to ensure that students receive a comprehensive education that includes e-learning resources. Continuous monitoring and evaluation should be conducted to assess the effectiveness of e-learning in improving academic performance.m-solving skills.